ANALISIS IKLAN KREATIF MIZONE VERSI BANTU SIAP BALIKIN PADA TIM KREATIF AGENSI RED COMMUNICATION - Sri Edi Teguh Lorosae (Universitas Mercu Buana, 2020)
In this study, researchers wanted to find out how the process of designing the creative ad of the Mizone version bantu siap balikin. This study uses a constructivist paradigm with a qualitative approach and case study methods. Data collection techniques were carried out through in-depth interviews with key informants and informants. The data validity checking technique uses source triangulation, namely by interviewing two sources, in this case Mizone customers, to obtain data validity. In this case, it can be seen that there are 3 stages carried out in the design of the Mizone version of the assistive creative advertisement, namely, the Pre-production, Production and Post-production stages. These three stages are the general process in making an advertisement. Each stage has an influence on the final results of the advertisements. The concepts and ideas of the ads are sought and then adjusted to the target audience of the ad. Advertising media is determined to have conformity with the target audience, so that the main target of advertising can be achieved. After the ad is displayed, the ad is then evaluated to determine the effect of the advertisement on the target audience (amplication).